2010
DOI: 10.1111/j.1476-5829.2010.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between l-CHOP and an l-CHOP protocol with interposed treatments of CCNU and MOPP (l-CHOP-CCNU-MOPP) for lymphoma in dogs

Abstract: An L-CHOP protocol with interposed treatments of CCNU and MOPP (L-CHOP-CCNU-MOPP) was evaluated in 66 dogs with stages III-V lymphoma. Results were compared with a historical group of 71 dogs treated with an L-CHOP protocol. Complete remission (CR) rates (85 and 80%, respectively) did not differ significantly between protocols (P = 0.48). First CR duration for dogs treated with L-CHOP-CCNU-MOPP was significantly longer: median, 317 days; 2-year CR rate, 35% versus median, 298 days; 2-year CR rate, 13%, P = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
56
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 29 publications
(48 reference statements)
3
56
1
Order By: Relevance
“…The adage ‘in on a gurney’ to describe a patient considered to be clinical substage b does not reflect how survey respondents report assigning clinical substage. The results of this study also do not conform with a published clinical study that stipulated that gastrointestinal or respiratory signs prior to treatment had to be severe enough to necessitate hospitalization for substage b designation . This could raise the question as to whether designation of substage b is too lenient in clinical practice and therefore may not have the same degree of prognostic utility.…”
Section: Discussioncontrasting
confidence: 78%
“…The adage ‘in on a gurney’ to describe a patient considered to be clinical substage b does not reflect how survey respondents report assigning clinical substage. The results of this study also do not conform with a published clinical study that stipulated that gastrointestinal or respiratory signs prior to treatment had to be severe enough to necessitate hospitalization for substage b designation . This could raise the question as to whether designation of substage b is too lenient in clinical practice and therefore may not have the same degree of prognostic utility.…”
Section: Discussioncontrasting
confidence: 78%
“…It is still unclear whether this medication contributed to the dramatic clinical deterioration observed, but it seems unlikely. Other chemotherapeutic medications might have been used, such as cytarabine or lomustine that are able to cross the bloodbrain barrier and thus are of great interest in treating malignancies involving the CNS [7,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Various CHOP-based protocols were published following these decades, all consisting of a CHOP-based induction phase, again followed by a prolonged maintenance phase (Teske and others 1990, Stone and others 1991, Keller and others 1993, Myers and others 1997, Zemann and others 1998, Kessler and Kandel 2004, Siedlecki and others 2006, Simon and others 2008, Daters and others 2010). Over the past 15 years, various studies have suggested that discontinuous polychemotherapy protocols ranging from 12 to 26 weeks total duration without a maintenance phase are equally or even more effective than the older continuous protocols with maintenance therapy (Chun and others 2000, Moore and others 2001, Garrett and others 2002, MacDonald and others 2005, Simon and others 2006, Hosoya and others 2007, Rassnick and others 2010, Simon 2010, Sorenmo and others 2010). However, this observation is based on relatively small numbers of dogs (n=24–130).…”
mentioning
confidence: 99%